Biochemical characterisation of the human Ccr4-Not complex: core complex assembly and deadenylation activity - Pavanello, Lorenzo (2018)
Targeted degradation of cytoplasmic mRNA is of fundamental importance for regulated gene expression in eukaryotic cells. The shortening and removal of the poly(A) tail (deadenylation) is the initial and often rate-limiting step in this process. Two key components in deadenylation are the PAN2-PAN3 and the Ccr4-Not complexes. PAN2-PAN3 is a trimer composed by two regulatory subunits (PAN3) and a catalytic enzyme (PAN2). The Ccr4-not complex is composed of at least eight subunits, constituting four modules, that bind the scaffold protein CNOT1: the N-terminal module (CNOT10, CNOT11); the catalytic nuclease module (Caf1, Ccr4); the CNOT9 module (CNOT9); and the NOT-module (CNOT2, CNOT3). A cellular and biochemical characterisation of the PAN2-PAN3 complex was planned, to further understand its role in eukaryotic cells and determine the deadenylation rates. Similarly, we have started to reconstitute the human Ccr4-Not to understand the contributions of the individual modules to the activity of the complex. Initially, we purified a recombinant nuclease module composed of Caf1, Ccr4, and the anti-proliferative protein BTG2. Next, we reconstituted a core complex including the nuclease module, CNOT9 and a segment of CNOT1 encompassing the MIF4G and DUF3819 domains (CNOT1M). Then, we compared the activity of the core complex and the nuclease module using substrates containing short (A9) and longer (A20 or A50) poly(A) tails, as well as poly(A) tails coated with the poly(A)-binding protein PABPC1. We observed that the CNOT9 module contributes to enhanced deadenylation and increased selectivity towards terminal adenosine residues. Finally, the influence of the melanoma-associated P131L amino acid substitution of CNOT9 was investigated with structural and biochemical approaches.